Assessing the Fisher, Mohler, and Millard Techniques of Cleft Lip Repair Surgery With Eye-Tracking Technology. (May 2019) - Kwong, Jeffrey W.; Cai, Lawrence Z.; Azad, Amee D.; Lorenz, H. Peter; Khosla, Rohit K.; Lee, Gordon K.; Nazerali, Rahim S.
Abstract : Background: Cleft lip repair is essential to restoring physiologic function and ensuring social and psychological well-being in children with orofacial clefts. It is important to critically study various techniques to understand the elements of the lip and nasal repair that contribute to favorable results. Here, we use eye-tracking technology to evaluate how viewers analyze images of cleft lips repaired by the Fisher, Millard, or Mohler techniques. Methods: Thirty viewers were shown 5 images without deformity and 5 images each of unilateral cleft lips repaired by the Fisher, Millard, or Mohler techniques. Viewers assessed the esthetic quality of images on a Likert scale while eye-tracking technology analyzed their gaze patterns. Results: Of the 3 repair techniques, viewers found Fisher repairs most esthetically pleasing (mean ± standard error, 6.91 ± 0.13). Mohler repairs were next most attractive at (6.47 ± 0.13), followed by Millard repairs at (5.60 ± 0.14). The proportion of time spent in fixed gaze on the nose and upper lip was greatest for Millard repairs (58.3% ± 0.4%) and least for Fisher repairs (51.9% ± 0.5%). Viewers fixated most frequently on the nose and upper lip in Millard repairs (83.2% ± 0.5%) and least frequently in Fisher repairs (75.3% ± 0.5%). When examining the Millard compared with Fisher and Mohler repairs, viewers spent more time and fixations on the ipsilateral lip, nose, and repair scar than on the contralateral lip. Conclusions: The esthetics of the Fisher repair appear to be favored as measured by Likert scores and gaze data. Eye-tracking technology may be a useful tool to assess outcomes in plastic surgery. Abstract : Supplemental digital content is available in the text.